Growth performance and biochemical composition of nineteen microalgae collected from different Moroccan reservoirs - IDRISSI ABDELKHALEK, EL. A.; MOHAMED, B.; MOHAMMED, A.M.; LOTFI, A. (Mediterranean Marine Science, 2016)
Macro- and microalgae have recently received much attention due to their valuable chemical constituents. In order to increase existing data, the authors studied nineteen microalgae species isolated from different reservoirs in the Fez region (northern Morocco), undertaking experiments to determine for each species the specific growth rate, their total amounts of proteins, carbohydrates and lipids and the influence of the growth phase on these chemical constituents. Conditions of cultivation were as follows: light intensity equal to 300 μmol photons m-2 s-1, with a temperature regime of 25/20°C (day/night) and a 16/8 (light/dark) photoperiod cycle. The growth rates of the nineteen studied species of microalgae showed a wide variation between species, ranging from 0.27 g l-1 d-1 for Chlamydomonas ovalis to 3.64 g l-1 d-1 for Chlorococcum wemmeri. Protein, carbohydrate and lipid contents varied greatly between taxa and within genera. Ankistrodesmus falcatus, Chlamydomonas ovalis, Chlorococcum sp., Hyaloraphidium contortum, Scenedesmus protuberans, and Synechocystis aquatilis tended to synthesize proteins, the concentrations exceeding 20% dry weight (DW). Ankistrodesmus falcatus, Ankistrodesmus sp., Chlorococcum wemmeri, Coenocystis sp., Isocystis sp., Lyngbya bergei, Oscillatoria amphibia, Polytoma papillatum, Scenedesmus protuberans, Scenedesmus sp. and Synechocystis aquatilis showed a high capacity for lipid storage, greater than 20% DW. For carbohydrate contents, only Scenedesmus protuberans and Scenedesmus quadricauda showed an excessive level compared to other scanned species with 29.21% and 24.76% DW, respectively.